Analysis of factors associated with the incidence of anemia in adolescent girls at the Muara Enim Health Center: A cross-sectional study - Cici Destiana; Ali Harokan; Chairil Zaman (Lentera Perawat, 2025)
Background Anemia among adolescent girls is a significant public health issue in Indonesia, including in Muara Enim District, with a steadily increasing prevalence. The causes of anemia are multifactorial, including knowledge, nutritional status, adherence to iron (Fe) tablet consumption, and economic status. Objective This study aims to identify the factors associated with the incidence of anemia among adolescent girls in the working area of Muara Enim Health Center, Muara Enim District, in 2025. Methods This research employed a quantitative cross-sectional design. A total of 95 respondents were purposively selected from the population of adolescent girls in the Muara Enim Public Health Center area in 2024. Data were collected using a structured questionnaire and medical records, and analyzed using univariate, bivariate (chi-square test), and multivariate (multiple logistic regression) methods. Results Most respondents experienced anemia (53.7%), had good knowledge (57.9%), normal nutritional status (97.0%), were non-adherent to Fe tablet consumption (53.7%), and came from families with income below the regional minimum wage (72.6%). Bivariate analysis showed that adherence to Fe tablet consumption (p = 0.00) and economic status (p = 0.00) were significantly associated with anemia incidence, while knowledge (p = 0.99) and nutritional status (p = 0.21) were not. Multivariate analysis identified economic status as the most dominant factor (p = 0.002; OR = 0.20), indicating that adolescent girls from families earning ≥ regional minimum wage had an 80% lower risk of anemia. Conclusion Adherence to Fe tablet consumption and economic status are key factors in preventing anemia among adolescent girls, with economic status being the most influential. Integrated interventions should focus on strengthening Fe supplementation adherence and empowering families economically to reduce anemia prevalence in this population